Comparison of response parameters of the organism to the load in sports karate disciplines kata and kumite - Sližik, M.; Michalov, L. (Slovak Journal of Sport Science, 2016)
As part of the grant project VEGA 1/0414/15, we have decided to summarize the findings of the variability in the level of loading, in sports Karate-do disciplines Kata and Kumite, as the possibilities of using diagnostic load in the elite sports training. Sports Karate belongs to the group of combat, strength-speed sports where the load structure of sports performance is characterised by irregular interval oscillations of load intensity. Load intensity in both of its disciplines, however, ranges from medium to maximum duration and the time during which the load continues in one duel in Kumite is 3 min. for males, and 2 min. for females. In Kata, the average duration of one combat routine is 2 min. During such kind of load, the metabolic coverage of energy in the form of ATP-CP, anaerobic glycoses and aerobic phosphorylation takes place in both cases. We have measured the heart rate by means of a telemetry system Polar team 2 during sports performance in kata and kumite under training conditions. It was found that on average, the cardiovascular system underwent higher load in kumite. The average maximum heart rate values for kumite were higher by 4 n.min-1. Furthermore, the average HR values for kata were 188 n.min-1 while in kumite it reached 192 n.min-1. By measuring the blood lactate concentration using the the Biosen C-Line Lactate Analyser device, we found out that the average maximum LA values immediately after load were higher for kata competitors than kumite competitors, reaching a difference of 2.3 mmol.l-1. A comparison of maximum and minimum average LA values span during load showed that the difference between the maximum and minimum was higher for kataperformance (9.8 mmol.l-1), while for kumite it amounted only to 5.7 mmol.l-